Prevalence of and risk factors for diabetic retinopathy among the patients with diabetes mellitus in Dharan municipality, Nepal - Pokharel, Shailesh Mani; Badhu, Badri Prasad; Sharma, Sanjib; Maskey, Robin (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: The individuals with diabetes have 29 times higher chance of becoming blind due to diabetic retinopathy than non-diabetic of similar age and gender. The knowledge on the factors for it can help detect the disease in its early course. The study was conducted with objectives to study the prevalence of diabetic retinopathy and its risk factors in a diabetic population. Materials and Methods: A community based cross-sectional study that involved 418 subjects with type 2 diabetes, living in the Dharan municipality of Nepal was carried out using convenient sampling method. Results: The prevalence of diabetic retinopathy was 38.8%. Prevalence of mild, moderate, severe and very severe non-proliferative diabetic retinopathy was 9.1%, 16.3%, 6.2% and 17.2% respectively. Prevalence of proliferative diabetic retinopathy and clinically significant macular edema was 3.8% and 1.9% respectively. Among the risk factors studied age, hypoglycemic drug intake, family history and duration of diabetes mellitus had a significant association with the occurrence of diabetic retinopathy (p<0.05). Conclusions: The prevalence of diabetic retinopathy in patients with diabetes mellitus was 38.8% and increase risk factors for it are age, hypoglycemic drug intake, family history of diabetes, duration of diabetes. JCMS Nepal. 2015;11(1): 17-21